An engineered multicellular stem cell niche for the 3D derivation of human myogenic progenitors from iPSCs. (15th June 2022) - Mashinchian, Omid; De Franceschi, Filippo; Nassiri, Sina; Michaud, Joris; Migliavacca, Eugenia; Aouad, Patrick; Metairon, Sylviane; Pruvost, Solenn; Karaz, Sonia; Fabre, Paul; Molina, Thomas; Stuelsatz, Pascal; et al.
Abstract: Fate decisions in the embryo are controlled by a plethora of microenvironmental interactions in a three‐dimensional niche. To investigate whether aspects of this microenvironmental complexity can be engineered to direct myogenic human‐induced pluripotent stem cell (hiPSC) differentiation, we here screened murine cell types present in the developmental or adult stem cell niche in heterotypic suspension embryoids. We identified embryonic endothelial cells and fibroblasts as highly permissive for myogenic specification of hiPSCs. After two weeks of sequential Wnt and FGF pathway induction, these three‐component embryoids are enriched in Pax7‐positive embryonic‐like myogenic progenitors that can be isolated by flow cytometry. Myogenic differentiation of hiPSCs in heterotypic embryoids relies on a specialized structural microenvironment and depends on MAPK, PI3K/AKT, and Notch signaling. After transplantation in a mouse model of Duchenne muscular dystrophy, embryonic‐like myogenic progenitors repopulate the stem cell niche, reactivate after repeated injury, and, compared to adult human myoblasts, display enhanced fusion and lead to increased muscle function. Altogether, we provide a two‐week protocol for efficient and scalable suspension‐based 3D derivation of Pax7‐positive myogenic progenitors from hiPSCs. Synopsis: Skeletal progenitors offer extensive self‐renewal capacity for muscle regeneration, but their niche context remains unclear and derivatization inefficient. This resource reports a novel heterotypic embryoid model for the generation of induced pluripotent stem cell (iPSC)‐derived human myogenic progenitors in a defined microenvironment, suggesting new therapeutic avenues and opportunities for in vitro screenings. A cell type screen identifies mouse growth‐arrested embryonic fibroblasts and endothelial cells as permissive niche components for the induction of Pax7 + myogenic cells. WNT/FGF stimulation supports hiPSC commitment to the mesodermal lineage. Heterotypic culture‐derived Pax7 + cells display embryonic characteristics, resist differentiation, and function as stem cells in vivo . Heterotypic culture‐induced Pax7 + cell production is scalable to bioreactor level. Abstract : A heterotypic suspension embryoid model enables scalable generation of Pax7 + skeletal muscle progenitors in a defined microenvironment.